The Diploma in Primary Emergency Care (DipEC) - a survey of its graduates, their perceptions & subsequent trends - Cloete, David Allan (Stellenbosch : Stellenbosch University, 2020)
Thesis (MFamMed)--Stellenbosch University, 2020.